Modified Landau–Placzek ratio of the liquid metal rubidium beyond hydrodynamics. (22nd March 2023) - Demmel, F; Morkel, Chr
Abstract: The intensity ratio of the Rayleigh line and the Brillouin lines can be derived within hydrodynamics and is known as the Landau–Placzek (LP) ratio. This ratio is directly related to the ratio of specific heats of the fluid. Within the microscopic wave vector range, which can be probed by inelastic neutron scattering, the intensity ratio for simple liquid metals deviates distinctly from the hydrodynamic prediction of the LP-ratio. We derive the intensity ratio from experimental data of liquid rubidium, which shows an enhanced LP-ratio by a factor 8 compared to the hydrodynamic prediction. This strong deviation indicates a further relaxation process in the microscopic wave vector range beyond hydrodynamics. That relaxation process is the viscoelastic reaction of the simple liquid to density fluctuations. Taking this process into account a modified LP-ratio is able to describe the data quite well.